The politics of economic policy reforms in Nigeria - Ibe, Aforka C. (Akwa: Levrene, 2000)
The book gave a brief report of the economic reforms by different regimes in Nigeria. It was produced as a result of the incessant demands of the postgraduate students which was validated by massive looting of public funds under the Abacha regime.
opc 19/12/16
Loans
Keywords: Economic policy; Economic reforms; Nigeria